2009
DOI: 10.4067/s0717-92002009000200001
|View full text |Cite
|
Sign up to set email alerts
|

Modelos fustales para renovales de roble, raulí y coigüe en Chile

Abstract: SUMMARYA total of ten individual tree taper models were fitted to felled raulí (Nothofagus alpina), roble (N. obliqua) and coigüe (N. dombeyi) trees, corresponding to total of 558 individuals (251, 180 and 127, respectively). They were selected from 108 sample plots of pure or mixed roble-raulí-coigüe second growth forests located between 36° and 42° S latitude in Chile. The taper models and a volume model were fitted to 12 fitting groups; these were defined according to the combinations of growth zone and spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 12 publications
(4 reference statements)
0
5
0
3
Order By: Relevance
“…Other studies also have found contrasting differences in growth between Nothofagus species and growth zones [5,9,10,[59][60][61][62][63][64]. The incorporation of species and/or zone factors to improve growth models has been previously reported [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies also have found contrasting differences in growth between Nothofagus species and growth zones [5,9,10,[59][60][61][62][63][64]. The incorporation of species and/or zone factors to improve growth models has been previously reported [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Regional changes in taper equations for N. obliqua were also studied. These differences in growth patterns (GEZAN et al 2009, ATTIS BELTRÁN et al 2015 supporting the idea to develop specific stem profile functions for Nothofagus alpina and N. obliqua in Lanin National Park. For this, the aim was to adjust taper equations to determine volumes of different timber products for commercial stems of N. alpina and N. obliqua.…”
Section: Introductionmentioning
confidence: 91%
“…The outputs generate more precise volume estimations, and are more efficient their use to build growth and yield models and sawmill simulators (GEZAN et al 2009). There are several types of equations (KOZAK, 2004;SÁNCHEZ GONZÁLEZ et al 2007;POMPA GARCÍA;SOLÍS MORENO, 2008;GEZAN et al 2009;ANDRADE, 2014), where the most commonly employed independent variables were: diameter at breast height (DBH), tree height, crown ratio, and pairs of diameter/height along the stem (HANN et al 1987). These variables are easy and are standard measurements during forest inventories.…”
Section: Introductionmentioning
confidence: 99%
“…La validación de los modelos fustales consideró la evaluación de la capacidad predictiva respecto a cuatro importantes atributos de este tipo de modelos: predicción de diámetros a cualquier altura fustal, predicción de alturas fustales para cualquier diámetro fustal, predicción de volúmenes acumulados hasta diversas alturas fustales y predicción de volúmenes acumulados hasta diversos diámetros fustales. En la mayoría de los estudios publicados, la comparación de modelos fustales se ha realizado considerando la evaluación de la capacidad para predecir diámetros fustales y volúmenes comerciales (Torrubiano y Salinas, 1998;Gezan et al, 2009). En este estudio se pretende analizar y evaluar de manera más completa cada uno de los modelos fustales seleccionados (Tabla 2).…”
Section: Evaluación Y Comparación De Modelosunclassified